Standard rodent diets differentially impact alcohol consumption, preference, and gut microbiome diversity - Zaparte, Aline; Dore, Evan; White, Selby; Paliarin, Franciely; Gabriel, Cameron; Copenhaver, Katherine; Basavanhalli, Samhita; Garcia, Emily; Vaddavalli, Rishith; Luo, Meng; Taylor, Christopher M.; Welsh, David Allen; et al. (Frontiers in Neuroscience, 2024)
Alcohol Use Disorder (AUD) is a complex and widespread disease with limited pharmacotherapies. Preclinical animal models of AUD use a variety of voluntary alcohol consumption procedures to recapitulate different phases of AUD including binge alcohol consumption and dependence. However, voluntary alcohol consumption in mice is widely variable rendering it difficult to reproduce results across labs. Accumulating evidence indicates that different brands of commercially available rodent chow can profoundly influence alcohol intake.In this study, we investigated the effects of three commercially available and widely used rodent diet formulations on alcohol consumption and preference in C57BL/6J mice using the 24h intermittent access procedure. The three brands of chow tested were LabDiet 5001 (LD 5001), LabDiet 5053 (LD 5053), and Teklad 2019S (TL2019S) from two companies (Research Diets and Envigo respectively). Mice fed LD5001 and LD5053 displayed higher levels of alcohol consumption and preference compared to mice fed TL2019S. We also found that alcohol consumption and preference could be rapidly switched by changing the diet 48h prior to alcohol administration. Sucrose, saccharin, and quinine preference were not altered suggesting that the diets did not alter sweet and bitter taste perception. We also found that mice fed LD5001 displayed increased quinine-resistant alcohol intake compared to mice fed TL2019S, suggesting that diets could influence the development of compulsive like alcohol consumption. We profiled the gut microbiome of water and alcohol drinking mice that were maintained on different diets and found significant differences in bacterial alpha and beta diversity, which could impact gut-brain axis signaling and alcohol consumption.